2011
DOI: 10.1111/j.1399-6576.2011.02435.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the pleth variability index to predict fluid responsiveness depends on the perfusion index

Abstract: The PVI was not able to predict fluid responsiveness with sufficient accuracy. In patients with higher perfusion states, the PVI improved its ability to predict haemodynamic changes, strongly suggesting a relevant influence of the PI on the PVI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 33 publications
5
80
3
1
Order By: Relevance
“…The site of measurement has an influence, 7 and PVI values also depend on PI values. 8,16 The present study confirms these findings; however, regardless of nerve blockade and vasomotor state, the application of a fluid bolus is reflected by a decrease in PVI values in both limbs.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The site of measurement has an influence, 7 and PVI values also depend on PI values. 8,16 The present study confirms these findings; however, regardless of nerve blockade and vasomotor state, the application of a fluid bolus is reflected by a decrease in PVI values in both limbs.…”
Section: Discussionsupporting
confidence: 88%
“…It is possible that the application of local anesthetics might result in changes in the state of peripheral perfusion, which could influence the accuracy of PVI to predict changes in preload reliably following volume expansion. 8 …”
Section: Résumémentioning
confidence: 99%
“…We have asserted that SVV values must be estimated cautiously during pneumoperitoneum (6). Pleth variability index (PVI) is another dynamic index, and many studies concluded that it is useful for the assessment of fluid responsiveness in patients (2,(7)(8)(9) although one study concluded that PVI seems inaccurate to predict fluid responsiveness after conventional…”
Section: Introductionmentioning
confidence: 99%
“…[86][87][88][89][90] The reasons for this paradox (excellent predictor of fluid responsiveness yet not in agreement with arterial-derived metrics) are not clear but may be related to the dependence of PVI on perfusion. 91 While the Masimo device may not be as effective as its more invasive counterparts during periods of malperfusion, it has three major advantages -relative low cost in comparison with its competitors, the ubiquity of pulse oximetry (which of course is a Canadian Anesthesiologists' Society basic monitoring standard), 92 and ease of use.…”
Section: Technological Assessmentmentioning
confidence: 99%